Some aspects concerning the financial security of the country - MIHAI, Ilie (Annals of Spiru Haret University. Economic Series, 2012)
Given the increasingly globalized economy, in which the inter-dependencies of economic, financial, social, cultural, environmental, as well as other issues are widening, the maintenance and defence of attributes pertaining to sovereignty, independence and national security of each country, become a real and worthy challenge. In other words, the question arises, how could a country, especially one such as Romania, located at the intersection of particularly important geostrategic interests, manager, to converse national attributes of sovereignty, independence and security, while also fulfilling its obligations deriving from international treaties and bodies at which it is a party.